Two-loop master integrals for e + e − → μ + μ − process with account of electron mass - Roman N. Lee (Journal of High Energy Physics)
Abstract We calculate a subset of two-loop master integrals relevant for the differential cross section of e + e − → μ + μ − process. We consider only those families for which the account of the electron mass m is necessary. Our results have the form of the Frobenius series in m with coefficients expressed via Goncharov’s polylogarithms.